2019
DOI: 10.29303/jitpi.v3i1.37
|View full text |Cite
|
Sign up to set email alerts
|

Diseases Characteristic of Pre-Weaning Bali Calf (Bos Javanicus) in Central Lombok, Indonesia

Abstract: The aim of the study was to evaluate Bali cattle pre-weaning calf death in Central Lombok. Sick calves were examined their condition, followed by physiology examination. Then feces and blood samples were collected and examined for internal parasites and hematology. The results showed that the newborn calf was 57,2% (61), while calves sick was 16.5% (101) consisted of 7,2% (57) death calves and 9,3% still alive. Calves examination showed that 21, 05 % (12) was under weak conditions, 38.5% (22) with high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In a study of diseases of pre-weaning calves in Central Lombok, Province of West Nusa Tenggara, diarrhoea dominated the clinical picture (42/57). However, only less than 2% (n = 42) of calves suffering from diarrhoea developed leukocytopenia, a possible indicator of viral disease [68]; the majority of sick calves in the study showed hypochromic anaemia (98.2%) and lymphocytosis (35.1%) [68]. These studies suggest that BVDV may play a role in diarrheic cases in Indonesian cattle, along with other causes.…”
Section: Impact Of Bvd On Cattle Production In Indonesiamentioning
confidence: 67%
“…In a study of diseases of pre-weaning calves in Central Lombok, Province of West Nusa Tenggara, diarrhoea dominated the clinical picture (42/57). However, only less than 2% (n = 42) of calves suffering from diarrhoea developed leukocytopenia, a possible indicator of viral disease [68]; the majority of sick calves in the study showed hypochromic anaemia (98.2%) and lymphocytosis (35.1%) [68]. These studies suggest that BVDV may play a role in diarrheic cases in Indonesian cattle, along with other causes.…”
Section: Impact Of Bvd On Cattle Production In Indonesiamentioning
confidence: 67%